Techno-economic viability analysis of gasification technology as a sustainable alternative for electric power generation from municipal solid waste - Menezes Neto,João Teles de (2021)
Abstract: The present study has analyzed the techno-economic feasibility of applying gasification technology to the energy use of Municipal Solid Waste in an industrial plant. In that case, the obtained gas shall be used as an alternative source for electric energy generation. The technical feasibility analysis took into account the waste suitability to the gasification process, as well as the gasification process efficiency, through tests carried out in a testing plant, and an estimation of electric power was obtained. The economic viability studied the indicators Net Present Value, Internal Rate of Return and Discounted Payback considering the cash flow estimation from plant installation and operation. A univariate sensitivity analysis of Net Present Value has considered the variables with influence on the cash flow, such as the Minimum Attractiveness Return Rate, energy tariff, installed power, operating and maintenance costs and the undertaking unitary cost. The results suggested the technical feasibility considering both the suitability of the waste for the process and its efficiency, which reached values of 62% allowing to reach an estimated electric power of 1.46 MW. The economic viability was verified under the studied conditions. The sensitivity analysis showed that the economic viability was sensitive to the variation of some parameters estimated on cash flow, which in turn leads to an understanding of the need for subsidies as an incentive to the technology effective viability. This study provides decisions makers with data and information on how to adopt the gasification technology in Brazil.